BCL-2 levels do not predict azathioprine treatment response in inflammatory bowel disease, but inhibition induces lymphocyte apoptosis and ameliorates colitis in mice. (21st September 2018) - Weder, B; Mozaffari, M; Biedermann, L; Mamie, C; Moncsek, A; Wang, L; Clarke, S H; Rogler, G; McRae, B L; Graff, C L; Ruiz, P A; Hausmann, M
Summary: In inflammatory bowel disease (IBD), inflammation is sustained by an exaggerated response of lymphocytes. This results from enhanced expression of anti-apoptotic B cell lymphoma (BCL-2) and BCL-XL associated with a diminished turnover. Azathioprine (AZA) directly targets BCL-2 family-mediated apoptosis. We investigated whether the BCL-2 family expression pattern could be used to predict treatment response to AZA and determined whether BCL-2 inhibitor A-1211212 effectively diminishes lymphocytes and ameliorates inflammation in a model of colitis. BCL-2 family expression pattern was determined by next-generation sequencing (NGS). BCL-2 inhibitor was administered orally to Il10-/- mice. Haematological analyses were performed with an ADVIA 2120 and changes in immune cells were investigated using quantitative polymerase chain reaction (qPCR) and fluorescence activated cell sorter (FACS). We determined similar expression levels of BCL-2 family members in patients with remission and patients refractory to treatment, showing that BCL-2 family expression can not predict AZA treatment response. Expression was not correlated with the modified Truelove and Witts activity index (MTWAI). BCL-2 inhibitor initiated cell death in T cells from patients refractory to AZA and reduced lymphocyte count in Il10-/- mice. FACS revealed diminished CD8 + T cells upon BCL-2 inhibitor in Il10-/- mice without influencing platelets. Tnf, Il1β, IfnƔ and Mcp-1 were decreased upon BCL-2 inhibitor. A-1211212 positively altered the colonic mucosa and ameliorated inflammation in mice. Pro-apoptotic BCL-2 inhibitor A-1211212 diminishes lymphocytes and ameliorates colitis in Il10-/- mice without inducing thrombocytopenia. BCL-2 inhibition could be a new therapy option for patients refractory to AZA. Graphical Abstract: